KEANEKARAGAMAN SERANGGA HAMA DAN SERANGANNYA PADA TUMBUHAN SUKU MYRTACEAE - Alya Okta Cahyaningrum; Riyanto Riyanto (BIO-EDU: Jurnal Pendidikan Biologi, 2023)
Myrtaceae tribe plants belong to a large group and are often found in various regions in Indonesia. This study aims to determine the diversity of insect pests and their attacks on plants belonging to the Myrtaceae family. The research was conducted by means of literature studies from various reputable articles. The results of the study found that among the types of pests, among others, Liriomyza spp, Sylepta spp, Acroceros syngramma, Cricula trifenestrata H., Liriomyza trifolii, Anselmella kerrichi, Hexamithodera semivelutina, Hyposidra talaca, Bactrocera sp., Bactrocera albistrigata, Bactrocera carambolae, Microtermes sp., Disosteira sp., Valanga nigricornis, Acherontia lachesis, dan Cosmoleptrus sp. Tumbuhan yang terserang hama antara lain Syzygium samarangense, Syzygium parameswaranii, Syzygium aromaticum, Syzygium luzonense, Syzygium aqueum, Psidium guajava, dan Melaleuca cajuputi. Pest attack causes leaf curl, spots on leaf surface, damage to leaf anatomy, hollow leaves, jagged leaf edges, holes in stem bark, wilted roots and roting fruit. The conclusion of this study is the diversity of insect pests that attack the Myrtaceae tribe, there are 16 types of insects.